2019
DOI: 10.1128/aac.02673-18
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Exposure-Effect Relationship of Liposomal Amphotericin B against Aspergillus fumigatus

Abstract: In vitro pharmacokinetic/pharmacodynamic data of liposomal amphotericin B (L-AMB) were compared with animal data from neutropenic and nonneutropenic models of azole-susceptible and azole-resistant invasive aspergillosis. L-AMB was equally effective. The in vitro fCmax (maximum concentration of free drug)/MIC ratio associated with 50% of maximal activity was 0.31 (0.29 to 0.33), similar to that in neutropenic but not nonneutropenic mice (0.11 [0.06 to 0.20]). Simulation analysis indicated that standard L-AMB do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The pharmacodynamics of L-AmB is poorly understood due to its complex pharmacokinetics [ 27 , 28 ]. Indeed, several measurements can be conducted: total AmB, protein bound drug, liposome associated drug, and freely circulating drug.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacodynamics of L-AmB is poorly understood due to its complex pharmacokinetics [ 27 , 28 ]. Indeed, several measurements can be conducted: total AmB, protein bound drug, liposome associated drug, and freely circulating drug.…”
Section: Resultsmentioning
confidence: 99%
“…Median plasma concentrations were 100 times lower twelve hours after the last nebulization in the inhalation group, who received 40 mg b.i.d for two days, compared to the oral group (400 mg b.i.d at day 1, 200 mg b.i.d at day 2) (8 vs. 1224 ng/mL, p < 0.0001) [ 137 ]. There was a non-significant trend towards a higher median ELF/plasma concentration ratio in the inhalation group (21, 95% CI [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ,…”
Section: Resultsmentioning
confidence: 99%
“…Deaguero et al [ 83 ] observed that nanoencapsulation of miconazole in cholesterol/sodium oleate vesicles have significant antifungal activity against several fungal pathogens. Siopi et al [ 84 ] have reported that the liposome-encapsulated amphotericin B possess significant therapeutic potential against mycotic respiratory infections in animals caused by A. fumigatus .…”
Section: Applications Of Nanoantifungals In Veterinary Medicinementioning
confidence: 99%
“…Salama et al (2016) evaluated the activity of cross-linked chitosan biguanidine (CChG) loaded with AgNPs. The thermal Clemons et al, 2005;Olson et al, 2006Olson et al, , 2010Olson et al, , 2015Lewis et al, 2007;Jung et al, 2009;Italia et al, 2011;Seyedmousavi et al, 2013;Siopi et al, 2019 In vivo (rabbits and mice) Sheikh et al, 2010.…”
Section: Aspergillosismentioning
confidence: 99%
“…At concentrations higher than 10 mg/kg/day there was no pharmacodynamic difference between the formulations. Regarding neutropenia, Siopi et al ( 2019 ), demonstrated in mice that the appropriate doses of AmBisome® range 1–3 mg/kg for non-neutropenic patients and 7.5–10 mg/kg for neutropenic patients with isolates of A. fumigatus with MIC from 0.5 to 1 mg/L.…”
Section: Current Scenario Of Nanotechnology In the Treatment And Vaccmentioning
confidence: 99%